Ocena czynników mających wpływ na podejmowanie aktywności fizycznej w trakcie studiów = Students’ attitude towards taking up physical activities apart from university classes - Duda, Mariola; Rżany, Michał; Dudło, Aleksandra; Dogońska, Aleksandra; Suszyński, Krzysztof; Górka, Dariusz (Journal of Education, Health and Sport, 2015)
Duda Mariola, Rżany Michał, Dudło Aleksandra, Dogońska Aleksandra, Suszyński Krzysztof, Górka Dariusz. Ocena czynników mających wpływ na podejmowanie aktywności fizycznej w trakcie studiów = Students’ attitude towards taking up physical activities apart from university classes. Journal of Education, Health and Sport. 2015;5(11):661-668. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35716 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A661-668 http://pbn.nauka.gov.pl/works/684967 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Original Text published © The Author (s) 2015. Duda Mariola, Rżany Michał, Dudło Aleksandra, Dogońska Aleksandra, Suszyński Krzysztof, Górka Dariusz. Ocena czynników mających wpływ na podejmowanie aktywności fizycznej w trakcie studiów. Quality in Sport. 2015;1(2):53-59. eISSN 2450-3118. The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. Mariola Duda, Michał Rżany, Aleksandra Dudło, Aleksandra Dogońska, Krzysztof Suszyński, Dariusz Górka Katedra Fizjoterapii, Zakład Medycyny Sportowej i Fizjologii Wysiłku Fizycznego Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach Ocena czynników mających wpływ na podejmowanie aktywności fizycznej w trakcie studiów Students’ attitude towards taking up physical activities apart from university classes Streszczenie Celem badania było odpowiedź na pytania: Od jakich czynników zależy podejmowanie aktywności fizycznej przez studentów poza uczelnia? Od czego zależy długość trwania ćwiczeń i w jakim okresie studiów jest on największy? Zbadano 301 studentów używając autorski kwestionariusz. Analiza polegała na wykonaniu statystyk opisowych oraz analizy wariancji ANOVA. Analiza wykazała zależność istotnie statystyczną pomiędzy płcią a podejmowaniem aktywności fizycznej. Mężczyźni częściej ćwiczą. Brak jest zależności pomiędzy częstością uprawiania sportu a płcią. Słowa kluczowe: student, aktywność fizyczna, studia. Abstract The aim of this study was to answer the following questions: What are the reasons that determine the physical activity of students outside of their university? What determines the duration of exercises and during what year the students exercise the most ? 301 students were tested using an original questionnaire. The analysis consisted of descriptive statistics and performed analysis ANOVA. Analysis showed a significant relationship between sex and physical activity. Men are more likely to exercise. However, there is no relationship between the frequency of physical activity and gender. Key words: student, physical activity, studies.